Incidencia jurídica de las contravenciones de tránsito leves de segunda clase, análisis de casos en el cantón Machala en los años 2007-2009. Propuesta de reforma al artículo 140 de la ley orgánica de transporte terrestre, tránsito y seguridad vial. - Abrigo Segarra, Magaly Aracely (2012)
The development of this thesis is a research work diagnosis - purposing which was aimed to determine contraventions of minor traffic second class in Machala, for which a methodological process based on inductive, deductive, descriptive methods developed, statistical, and hypothetical. Regarding the use of techniques interview, survey and signing they are used. The investigative process allowed to conclude the principal legal effects of contraventions of minor traffic second class in Machala, are scarce law enforcement, increasing the number of traffic violations due to the lack of precaution the drivers.